Pyscho social profile of the freshmen of e.a.p. international business san marcos: evaluations of emotional intelligence and demographic characteristics - Pérez Palacios, Emma Emilia (2017)
The objective of this research is to determine and visualize the relationship between the profile of emotional intelligence and socio-demographics of students admitted in 2013 at the EAP International business in San Marcos University. Similarly, evaluating and describing the distribution of students according to the main components of Emotional Intelligence. The research is no experimental and correlational cross -type basic design, applying descriptive statistics in a population of 101 of the 120 students. To collect the data, a socio-demographic questionnaire was applied, while the psychometric instrument was the Test of Emotional Intelligence taken from the famous inventory Baron (EQ-I). This test is based on five components called emotional quotient (EQ):1. Self –Awareness, Assertiveness, Self-Concept, Self-Empowerment and Independence. 2. The IQ interpersonal includes: Empathy, interpersonal relations and social responsibility. 3. Adaptability: Proof of reality and flexibility. 4. How to manipulate the stress. 5. Mood in general, including happiness and optimism. The overall result obtained from the study indicates that 2013 entrants have an average level of emotional intelligence the same is repeated in each component.The study demonstrates the need for project management and productivity articulate theory and practice of vocational training and personal development, on the transverse axis emotional intelligence, stimulating the skills, abilities and competencies towards achievement of excellence and competitiveness in the student population evaluated.